The Root Issues of Not Achieving an Unqualified Opinion: The Case Study in Local Governments XX of Indonesia - Ismail Saleh; Yan Rahadian (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study analyzed the root issues of the Local government XX of Indonesia failing to obtain an Unqualified Opinion. The method used in this research was a qualitative method with a case study approach. This study was conducted to map findings and analyze the main issues of the regional government failing to obtain an unqualified opinion. The scope of the study was limited by using Local Government Financial Reports From 2013 to 2019 and Audit Report from 2014 to 2020. This study was conducted on Local Government XX which had never once received an unqualified opinion. The result of the study indicated that the issues obtained from mapping the findings of violations of account problems, internal control systems, and compliance were caused by the weak competence of human resources owned by Local Government XX. The main problem occurred at the financial administration level at the Local Government Work Unit level and the weak supervision at each tiered level.